Mortality after liver surgery in Germany. Issue 11 (24th July 2019) - Filmann, N.; Walter, D.; Schadde, E.; Bruns, C.; Keck, T.; Lang, H.; Oldhafer, K.; Schlitt, H. J.; Schön, M. R.; Herrmann, E.; Bechstein, W. O.; Schnitzbauer, A. A.
Abstract : Background: Mortality rates after liver surgery are not well documented in Germany. More than 1000 hospitals offer liver resection, but there is no central regulation of infrastructure requirements or outcome quality. Methods: Hospital mortality rates after liver resection were analysed using the standardized hospital discharge data (Diagnosis‐Related Groups, ICD‐10 and German operations and procedure key codes) provided by the Research Data Centre of the Federal Statistical Office and Statistical Offices of the Länder in Wiesbaden, Germany. Results: A total of 110 332 liver procedures carried out between 2010 and 2015 were identified. The overall hospital mortality rate for all resections was 5·8 per cent. The mortality rate among 17 574 major hepatic procedures was 10·4 per cent. Patients who had surgery for colorectal liver metastases (CRLMs) had the lowest mortality rate among those with malignancy (5·5 per cent), followed by patients with gallbladder cancer (7·1 per cent), hepatocellular carcinoma (9·3 per cent) and intrahepatic cholangiocarcinoma (11·0 per cent). Patients with extrahepatic cholangiocarcinoma had the highest mortality rate (14·6 per cent). The mortality rate for extended hepatectomy was 16·2 per cent and the need for a biliodigestive anastomosis increased this to 25·5 per cent. Failure to rescue after complications led to mortality rates of more than 30 per cent in some subgroups. There was a significant volume–outcome relationship for CRLM surgery in very high‐volume centres (mean 26–60 major resections for CRLMs per year). The mortality rate was 4·6 per cent in very high‐volume centres compared with 7·5 per cent in very low‐volume hospitals (odds ratio 0·60, 95 per cent c.i. 0·42 to 0·77; P < 0·001). Conclusion: This analysis of outcome data after liver resection in Germany suggests that hospital mortality remains high. There should be more focused research to understand, improve or justify factors leading to this result, and consideration of centralization of liver surgery. Abstract : Mortality following liver surgery has been analysed using data from the Federal Statistical Office from 2010 to 2015. Overall mortality in more than 100 000 resections was 5·8 per cent, and that after major resections was 10·4 per cent. A volume–outcome relationship was evident after major resections for colorectal liver metastases (CRLMs) in centres performing more than 25 major resections per year, with the mortality rate decreasing from more than 6·5 per cent to 4·6 per cent. DRG, Diagnosis‐Related Groups; ECC, extrahepatic cholangiocarcinoma; BDA, biliodigestive anastomosis. Case for centralilzation of liver surgery Abstract : Antecedentes: En Alemania, los datos de mortalidad después de la cirugía no están bien documentados. En más de 1.000 hospitales se realizan resecciones hepáticas, pero no existe una regulación central de los prerrequisitos estructurales necesarios y de la calidad de los resultados. Métodos: Las tasas de mortalidad hospitalaria relacionadas con las resecciones hepáticas se analizaron utilizando los datos estandarizados del alta hospitalaria (Diagnóstico de grupos relacionados, DRG), la clasificación internacional de enfermedades 10 (ICD10) y la clave de procedimientos y operaciones (códigos OPS) proporcionados por el RDC de la Oficina Federal de Estadística y Oficinas de Estadística de Länder en Wiesbaden, Alemania. Resultados: Se identificaron un total de 110.332 procedimientos hepáticos (de 2010 a 2015). La tasa global de mortalidad hospitalaria para todas las resecciones fue del 5, 8%. Las resecciones hepáticas mayores ( n = 15.333) presentaron una mortalidad del 10, 4%. Los pacientes con metástasis hepáticas colorrectales ( colorectal liver metastases, CRLM) tuvieron la mortalidad más baja de entre los pacientes con neoplasias malignas (5, 5%), seguidos de los pacientes con cáncer de vesícula biliar (7, 1%), colangiocarcinoma intrahepático ( intrahepatic colangiocarcinoma, iCC) (11, 0%) y carcinoma hepatocelular ( hepatocellular carcinoma, HCC) (9, 3%). Los pacientes con colangiocarcinoma extrahepático ( extrahepatic cholangiocarcinoma, eCC) presentaron la mortalidad más alta (14, 6%). Las hepatectomías extendidas (16, 2%) y la necesidad de una anastomosis biliodigestiva ( biliodigestive anastomosis, BDA) aumentaron la mortalidad a un 25, 5%. La falta de solución de algunas complicaciones llevó a tasas de mortalidad de más del 30% en algunos subgrupos. Hubo una relación significativa volumen‐resultado para las CRLM en centros de alto volumen (25, 3 a 59, 7 resecciones mayores/año; razón de oportunidades, odds ratio, OR 0, 60, i.c. del 95%: 0, 42‐0, 77; P < 0, 001), lo que resultó en una disminución en las tasas de mortalidad de 7, 5/6, 4/7, 5/6, 5% a 4, 6%. Conclusión: El análisis de los resultados después de la resección hepática en Alemania muestra una alta mortalidad hospitalaria inesperada. Este análisis indica la necesidad de efectuar una investigación más específica para comprender, mejorar o justificar los factores que determinan estos hallazgos.